Nutrient dynamics and buffering capacity of coastal groundwater-dependent microbialite ecosystems - Carla Dodd; Hayley C. Cawthra; Gudrun Massmann; Janine B. Adams; Callum R. Anderson; Lucienne R.D. Human; Daniel A. Lemley; Tristin W. O'Connell; Gavin M. Rishworth (Estuarine, Coastal and Shelf Science, 2026)

Modelling UK air quality implications of decarbonisation using hydrogen - Adam Brighty; Francisca Jalil-Vega; Nicolás Ripoll Kameid; Seokyoung Kim; Tim Oxley; Daniel Mehlig; Mike Holland; Paul E. Dodds; Helen ApSimon (Energy Policy, 2026)

Navigating danger: Watercraft-related mortality of sea turtles in the United States Atlantic and Gulf coastal waters - Mariana M.P.B. Fuentes; Brian A. Stacy; Susan G. Barco; Robert A. DiGiovanni; Karen M. Dourdeville; Kimberly F. Durham; Mark Faherty; Sarah A. Finn; Allen M. Foley; Matthew H. Godfrey; Robert F. Hardy; Lyndsey N. Howell; et al. (Biological Conservation, 2025)

Thermal degradation of polyvinyl chloride in the presence of lead oxide: A kinetic and mechanistic investigation - Sanad Altarawneh; Mohammad Al-Harahsheh; Labeeb Ali; Mohammednoor Altarawneh; Oday H. Ahmed; Adam Buttress; Chris Dodds; Sam Kingman (Chemical Engineering Journal, 2024)

The special sauce of the Cancer Prevention and Control Research Network: 20 years of lessons learned in developing the evidence base, building community capacity, and translating research into practice - Stephanie B. Wheeler; Rebecca J. Lee; Alexa L. Young; Adam Dodd; Charlotte Ellis; Bryan J. Weiner; Kurt M. Ribisl; Prajakta Adsul; Sarah A. Birken; María E. Fernández; Peggy A. Hannon; James R. Hébert; et al. (Cancer Causes & Control, 2023)
Purpose The Cancer Prevention and Control Research Network (CPCRN) is a national network focused on accelerating the translation of cancer prevention and control research evidence into practice through collaborative, multicenter projects in partnership with diverse communities. From 2003 to 2022, the CPCRN included 613 members. Methods We: (1) characterize the extent and nature of collaborations through a bibliometric analysis of 20 years of Network publications; and (2) describe key features and functions of the CPCRN as related to organizational structure, productivity, impact, and focus on health equity, partnership development, and capacity building through analysis of 22 in-depth interviews and review of Network documentation. Results Searching Scopus for multicenter publications among the CPCRN members from their time of Network engagement yielded 1,074 collaborative publications involving two or more members. Both the overall number and content breadth of multicenter publications increased over time as the Network matured. Since 2004, members submitted 123 multicenter grant applications, of which 72 were funded (59%), totaling more than $77 million secured. Thematic analysis of interviews revealed that the CPCRN’s success—in terms of publication and grant productivity, as well as the breadth and depth of partnerships, subject matter expertise, and content area foci—is attributable to: (1) its people–the inclusion of members representing diverse content-area interests, multidisciplinary perspectives, and geographic contexts; (2) dedicated centralized structures and processes to enable and evaluate collaboration; and (3) focused attention to strategically adapting to change. Conclusion CPCRN’s history highlights organizational, strategic, and practical lessons learned over two decades to optimize Network collaboration for enhanced collective impact in cancer prevention and control. These insights may be useful to others seeking to leverage collaborative networks to address public health problems.

Determining the feasibility of characterising cellular senescence in human skeletal muscle and exploring associations with muscle morphology and physical function at different ages: findings from the MASS_Lifecourse Study - Leena Habiballa; Adam Hruby; Antoneta Granic; Richard M. Dodds; Susan J. Hillman; Diana Jurk; João F. Passos; Avan A. Sayer (GeroScience, 2023)
Cellular senescence may be associated with morphological changes in skeletal muscle and changes in physical function with age although there have been few human studies. We aimed to determine the feasibility of characterising cellular senescence in skeletal muscle and explored sex-specific associations between markers of cellular senescence, muscle morphology, and physical function in participants from the MASS_Lifecourse Study. Senescence markers ( p16 , TAF (Telomere-Associated DNA Damage Foci), HMGB1 (High Mobility Group Box 1), and Lamin B1) and morphological characteristics (fibre size, number, fibrosis, and centrally nucleated fibres) were assessed in muscle biopsies from 40 men and women (age range 47–84) using spatially-resolved methods (immunohistochemistry, immunofluorescence, and RNA and fluorescence in situ hybridisation). The associations between senescence, morphology, and physical function (muscle strength, mass, and physical performance) at different ages were explored. We found that most senescence markers and morphological characteristics were weakly associated with age in men but more strongly, although non-significantly, associated with age in women. Associations between senescence markers, morphology, and physical function were also stronger in women for HMGB1 and grip strength ( r = 0.52); TAF, BMI, and muscle mass ( r > 0.4); Lamin B1 and fibrosis ( r = − 0.5); fibre size and muscle mass ( r ≥ 0.4); and gait speed ( r = − 0.5). However, these associations were non-significant. In conclusion, we have demonstrated that it is feasible to characterise cellular senescence in human skeletal muscle and to explore associations with morphology and physical function in women and men of different ages. The findings require replication in larger studies.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A comparison of trends in population size and life history features of Atlantic salmon (Salmo salar) and anadromous and non-anadromous Brown trout (Salmo trutta) in a single catchment over 116 years - Colin E. Adams; Hannele M. Honkanen; Ellen Bryson; Isabel E. Moore; Malcolm MacCormick; Jennifer A. Dodd (Hydrobiologia, 2022)
We use a long time series of catch abundance from a recreational fishery over 116 years to look for population trends in Atlantic salmon, and anadromous (sea trout) and non-anadromous (brown) trout for a single catchment, Loch Lomond, west central Scotland. Year strongly predicted variation in catches but catch effort did not meaningfully increase explained variation. Salmon showed periods of increasing and decreasing trends, for sea trout and brown trout there was an overall declining trend. Since 1952, Lomond salmon population trends differed from both wider Scotland and southern Europe, indicating that the Lomond population is partially buffered from drivers of change in salmon populations more widely. In contrast Lomond sea trout showed a similar declining trend to that of populations from the wider west of Scotland over this period. The Lomond populations showed some evidence of shorter-term cycling patterns; the drivers for which are unknown. Body size in salmon and sea trout declined but increased in brown trout; salmon returned to freshwater later, and the relative proportion of all caught trout that were anadromous increased across the time series. This study shows a long and protracted period of fundamental change to populations of these two species over 116 years.

Shifting stoichiometry: Long‐term trends in stream‐dissolved organic matter reveal altered C:N ratios due to history of atmospheric acid deposition - Bianca M. Rodríguez‐Cardona; Adam S. Wymore; Alba Argerich; Rebecca T. Barnes; Susana Bernal; E. N. Jack Brookshire; Ashley A. Coble; Walter K. Dodds; Hannah M. Fazekas; Ashley M. Helton; Penny J. Johnes; Sherri L. Johnson; et al. (Global Change Biology, 2022)
Dissolved organic carbon (DOC) and nitrogen (DON) are important energy and nutrient sources for aquatic ecosystems. In many northern temperate, freshwater systems DOC has increased in the past 50 years. Less is known about how changes in DOC may vary across latitudes, and whether changes in DON track those of DOC. Here, we present long‐term DOC and DON data from 74 streams distributed across seven sites in biomes ranging from the tropics to northern boreal forests with varying histories of atmospheric acid deposition. For each stream, we examined the temporal trends of DOC and DON concentrations and DOC:DON molar ratios. While some sites displayed consistent positive or negative trends in stream DOC and DON concentrations, changes in direction or magnitude were inconsistent at regional or local scales. DON trends did not always track those of DOC, though DOC:DON ratios increased over time for ~30% of streams. Our results indicate that the dissolved organic matter (DOM) pool is experiencing fundamental changes due to the recovery from atmospheric acid deposition. Changes in DOC:DON stoichiometry point to a shifting energy‐nutrient balance in many aquatic ecosystems. Sustained changes in the character of DOM can have major implications for stream metabolism, biogeochemical processes, food webs, and drinking water quality (including disinfection by‐products). Understanding regional and global variation in DOC and DON concentrations is important for developing realistic models and watershed management protocols to effectively target mitigation efforts aimed at bringing DOM flux and nutrient enrichment under control.

First confirmed complete incubation of a flapper skate ( Dipturus intermedius ) egg in captivity - Steven Benjamins; Georgina Cole; Adam Naylor; James A. Thorburn; Jane Dodd (Journal of Fish Biology, 2021)
An egg of the critically endangered flapper skate Dipturus intermedius was successfully incubated to hatching in captivity in what is believed to be a first for the species. Water conditions (temperature, salinity, flow rate) were recorded, with mean water temperatures ranging from a monthly mean of 8.3 ± 1.2 to 13.2 ± 0.3°C and salinity from a monthly mean of 30.5 ± 1.2 to 36.6 ± 2.3 ppt. Hatching occurred after 534 days, suggesting that flapper skate eggs take c . 5700 growing degree‐days to incubate to hatching. The egg's prolonged embryonic development raises concerns about flapper skate eggs' vulnerability to anthropogenic disturbance.

Nanogeochemistry of hydrothermal magnetite - Artur P. Deditius; Martin Reich; Adam C. Simon; Alexandra Suvorova; Jaayke Knipping; Malcolm P. Roberts; Sergey Rubanov; Aaron Dodd; Martin Saunders (Contributions to Mineralogy and Petrology, 2018)

The influence of aquaculture unit proximity on the pattern of Lepeophtheirus salmonis infection of anadromous Salmo trutta populations on the isle of Skye, Scotland - I. Moore; J. A. Dodd; M. Newton; C. W. Bean; I. Lindsay; P. Jarosz; C. E. Adams (Journal of Fish Biology, 2018)
A total of 230 anadromous Salmo trutta (brown trout) were sampled in five sheltered coastal fjords (or sea lochs) on the Isle of Skye, Scotland, U.K., in 2016 at varying distances from active Atlantic salmon Salmo salar farms. Statistical models were developed to investigate potential correlations between salmon lice Lepeophtheirus salmonis burdens on S. trutta hosts and their proximity to S. salar farm cages. Significant correlations were found between lice burdens and fish fork length and proximity to the nearest S. salar farm. The probability of the presence of L. salmonis on fish hosts increased with fish host size and with distance from the nearest S. salar farm, but total lice burdens were highest in fish sampled near S. salar farms and decreased with distance. The proportion of different life‐cycle stages of L. salmonis were also dependent on S. salar farm proximity, with higher juvenile lice numbers recorded at sites near S. salar farm cages. These results highlight the complexity of the relationship between S. trutta and L. salmonis infections on wild fish and emphasize the requirement of further research to quantify these effects to better inform conservation and management strategies, particularly in areas of active S. salar farm facilities.

The impact of a small-scale riverine obstacle on the upstream migration of Atlantic Salmon - M. Newton; J. A. Dodd; J. Barry; P. Boylan; C. E. Adams (Hydrobiologia, 2018)

The effect of foraging and ontogeny on the prevalence and intensity of the invasive parasite Anguillicola crassus in the European eel Anguilla anguilla - J Barry; M Newton; J A Dodd; D Evans; J Newton; C E Adams (Journal of Fish Diseases, 2017)
Infection patterns of the invasive Anguillicola crassus nematode were investigated in a population of the European eel Anguilla anguilla where parasite invasion is very recent , Loch Lomond, Scotland. Intensity levels of the parasite were associated with differences in fish ontogeny and trophic ecology. Although eels foraged on both fish and invertebrates, individuals which were smaller and fed on invertebrates (>70% contribution to diet) were found to contain a greater number of swim bladder parasites compared to larger eel with a predominance of fish (>60% contribution) in their diet. Within affected fish, a significant negative relationship was found between fish length and parasite intensity, with smaller individuals having higher parasite intensity than larger individuals. This study indicates that food intake and infection risk are linked in this recently infected host–parasite system. From a management perspective increasing our understanding of how infection intensity and repeated exposure is linked to resource use in an ecosystem is important for the future management of this endangered species in Europe.

Does size matter? A test of size‐specific mortality in Atlantic salmon Salmo salar smolts tagged with acoustic transmitters - M. Newton; J. Barry; J. A. Dodd; M. C. Lucas; P. Boylan; C. E. Adams (Journal of Fish Biology, 2016)
Mortality rates of wild Atlantic salmon Salmo salar smolts implanted with acoustic transmitters were assessed to determine if mortality was size dependent. The routinely accepted, but widely debated, ‘2% transmitter mass: body mass’ rule in biotelemetry was tested by extending the transmitter burden up to 12·7% of body mass in small [mean fork length ( L F ) 138·3 mm, range 115–168 mm] downstream migrating S. salar smolts. Over the short timescale of emigration (range 11·9–44·5 days) through the lower river and estuary, mortality was not related to S. salar size, nor was a relationship found between mortality probability and transmitter mass: body mass or transmitter length: L F ratios. This study provides further evidence that smolt migration studies can deviate from the ‘2% rule’ of thumb, to more appropriate study‐specific measures, which enables the use of fishes representative of the body size in natural populations without undue effects.

Lake bathymetry and species occurrence predict the distribution of a lacustrine apex predator - M. R. Hughes; J. A. Dodd; P. S. Maitland; C. E. Adams (Journal of Fish Biology, 2016)
This study examined the abiotic and biotic characteristics of ecosystems that allow expression of a life history called ferox trout, the colloquial name given to brown trout Salmo trutta adopting a piscivorous life history strategy, an apex predator in post‐glacial lakes in northern Europe. One hundred and ninety‐two lakes in Scotland show evidence of currently, or historically, supporting ferox S. trutta ; their presence was predicted in logistic models by larger and deeper lakes with a large catchment that also support populations of Arctic charr Salvelinus alpinus .

Foraging specialisms influence space use and movement patterns of the European eel Anguilla anguilla - J. Barry; M. Newton; J. A. Dodd; O. E. Hooker; P. Boylan; M. C. Lucas; C. E. Adams (Hydrobiologia, 2016)

Inter and intra‐population phenotypic and genotypic structuring in the European whitefish Coregonus lavaretus , a rare freshwater fish in Scotland - C. E. Adams; C. W. Bean; J. A. Dodd; A. Down; E. C. Etheridge; A. R. D. Gowans; O. Hooker; R. Knudsen; A. A. Lyle; I. J. Winfield; K. Præbel (Journal of Fish Biology, 2016)
This study revealed between‐lake genetic structuring between Coregonus lavaretus collected from the only two native populations of this species in Scotland, U.K. (Lochs Eck and Lomond) evidenced by the existence of private alleles (12 in Lomond and four in Eck) and significant genetic differentiation ( F ST = 0·056) across 10 microsatellite markers. Juvenile C. lavaretus originating from eggs collected from the two lakes and reared in a common‐garden experiment showed clear phenotypic differences in trophic morphology ( i.e . head and body shape) between these populations indicating that these characteristics were, at least partly, inherited. Microsatellite analysis of adults collected from different geographic regions within Loch Lomond revealed detectable and statistically significant but relatively weak genetic structuring ( F ST = 0·001–0·024) and evidence of private alleles related to the basin structure of the lake. Within‐lake genetic divergence patterns suggest three possibilities for this observed pattern: (1) differential selection pressures causing divergence into separate gene pools, (2) a collapse of two formerly divergent gene pools and (3) a stable state maintained by balancing selection forces resulting from spatial variation in selection and lake heterogeneity. Small estimates of effective population sizes for the populations in both lakes suggest that the capacity of both populations to adapt to future environmental change may be limited.

Freshwater and coastal migration patterns in the silver‐stage eel Anguilla anguilla - J. Barry; M. Newton; J. A. Dodd; M. C. Lucas; P. Boylan; C. E. Adams (Journal of Fish Biology, 2016)
The unimpeded downstream movement patterns and migration success of small female and male Anguilla anguilla through a catchment in north‐west Europe were studied using an acoustic hydrophone array along the River Finn and into the Foyle Estuary in Ireland. Twenty silver‐stage A. anguilla (total length, L T , range: 332–520 mm) were trapped 152 km upstream from a coastal marine sea‐lough outlet and internally tagged with acoustic transmitters of which 19 initiated downstream migration. Migration speed was highly influenced by river flow within the freshwater ( FW ) compartment. Anguilla anguilla activity patterns were correlated with environmental influences; light, tidal direction and lunar phase all influenced the initiation of migration of tagged individuals. Migration speed varied significantly between upstream and lower river compartments. Individuals migrated at a slower speed in transitional water and sea‐lough compartments compared with the FW compartment. While 88·5% survival was recorded during migration through the upper 121 km of the river and estuary, only 26% of A. anguilla which initiated downstream migration were detected at the outermost end of the acoustic array. Telemetry equipment functioned efficiently, including in the sea‐lough, so this suggests high levels of mortality during sea‐lough migration, or less likely, long‐term sea‐lough residence by silver A. anguilla emigrants. This has important implications for eel management plans.

Local scale, coastal currents influence recruitment to freshwater populations in the European eel Anguilla anguilla : a case study from the Isle of Man - J. Barry; K. Mcharg; J. A. Dodd; C. E. Adams (Journal of Fish Biology, 2015)
This study examines juvenile Anguilla anguilla ( P

Introduced parasite Anguillicola crassus infection significantly impedes swim bladder function in the European eel Anguilla anguilla (L.) - J Barry; J McLeish; J A Dodd; J F Turnbull; P Boylan; C E Adams (Journal of Fish Diseases, 2014)